Impact of minimally invasive surgery on surgeon health (ISSUE) study: protocol of a single-arm observational study conducted in the live surgery setting - Shaun Barber; Baljit Singh; Esther L Moss; Anumithra Amirthanayagam; Massimiliano Zecca (BMJ Open, 2023)
Introduction The rapid evolution of minimally invasive surgery has had a positive impact on patient outcomes; however, it is reported to be associated with work-related musculoskeletal symptoms (WMS) in surgeons. Currently there is no objective measure to monitor the physical and psychological impact of performing a live surgical procedure on the surgeon.Methods and analysis A single-arm observational study with the aim of developing a validated assessment tool to quantify the impact of surgery (open/laparoscopic/robotic-assisted) on the surgeon. Development and validation cohorts of major surgical cases of varying levels of complexity performed by consultant gynaecological and colorectal surgeons will be recruited. Recruited surgeons wear three Xsens DOT monitors (muscle activity) and an Actiheart monitor (heart rate). Salivary cortisol levels will be taken and questionnaires (WMS and State-Trait Anxiety Inventory) completed by the participants preoperatively and postoperatively. All the measures will be incorporated to produce a single score that will be called the 'S-IMPACT' score.Ethics and dissemination Ethical approval for this study has been granted by the East Midlands Leicester Central Research Ethics Committee REC ref 21/EM/0174. Results will be disseminated to the academic community through conference presentations and peer-reviewed journal publications. The S-IMPACT score developed within this study will be taken forward for use in definitive multicentre prospective randomised control trials.